Covariation MS uncovers a protein that controls cysteine catabolism - Haopeng Xiao; Martha Ordonez; Emma C. Fink; Taylor A. Covington; Hilina B. Woldemichael; Junyi Chen; Mika Sarkin Jain; Milan H. Rohatgi; Shelley M. Wei; Nils Burger; Muneeb A. Sharif; Julius Jan; et al. (Nature, 2025)
Abstract The regulation of metabolic processes by proteins is fundamental to biology and yet is incompletely understood. Here we develop a mass spectrometry (MS)-based approach that leverages genetic diversity to nominate functional relationships between 285 metabolites and 11,868 proteins in living tissues. This method recapitulates protein–metabolite functional relationships mediated by direct physical interactions and local metabolic pathway regulation while nominating 3,542 previously undescribed relationships. With this foundation, we identify a mechanism of regulation over liver cysteine utilization and cholesterol handling, regulated by the poorly characterized protein LRRC58. We show that LRRC58 is the substrate adaptor of an E3 ubiquitin ligase that mediates proteasomal degradation of CDO1, the rate-limiting enzyme of the catabolic shunt of cysteine to taurine 1 . Cysteine abundance regulates LRRC58-mediated CDO1 degradation, and depletion of LRRC58 is sufficient to stabilize CDO1 to drive consumption of cysteine to produce taurine. Taurine has a central role in cholesterol handling, promoting its excretion from the liver 2 , and we show that depletion of LRRC58 in hepatocytes increases cysteine flux to taurine and lowers hepatic cholesterol in mice. Uncovering the mechanism of LRRC58 control over cysteine catabolism exemplifies the utility of covariation MS to identify modes of protein regulation of metabolic processes.